2014
DOI: 10.18632/oncotarget.1734
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Aerobic Glycolysis and HIF-1α Expression Enhance Imiquimod-induced Apoptosis in Cancer Cells

Abstract: Tumor cells rely on aerobic glycolysis to maintain unconstrained cell growth and proliferation. Imiquimod (IMQ), a synthetic Toll-like receptor (TLR) 7/8 ligand, exerts anti-tumor effects directly by inducing cell death in cancer cells and/or indirectly by activating cellular immune responses against tumor cells. However, whether IMQ modulates glucose metabolism pathways remains unclear. In this study, we demonstrated that IMQ can enhance aerobic glycolysis by up-regulating HIF-1α expression at the transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 62 publications
6
36
0
Order By: Relevance
“…We previously demonstrated that IMQ dramatically depleted the intracellular ATP content in cancer cell lines [16], and consistently, IMQ treatment significantly decreased the ATP content in other tested cells ( Fig. 2A).…”
Section: Imq Depletes Cellular Atp and Activates Ampk Via Lkb1 Signalingsupporting
confidence: 76%
See 2 more Smart Citations
“…We previously demonstrated that IMQ dramatically depleted the intracellular ATP content in cancer cell lines [16], and consistently, IMQ treatment significantly decreased the ATP content in other tested cells ( Fig. 2A).…”
Section: Imq Depletes Cellular Atp and Activates Ampk Via Lkb1 Signalingsupporting
confidence: 76%
“…Additionally, the IMQinduced up-regulation of aerobic glycolysis is an adaptive response that protects cancer cells from IMQ-induced metabolic stress, particularly ATP depletion [16]. Thus, we hypothesized that IMQinduced metabolic stress not only activates AMPK but also induces AMPK-dependent apoptosis and/or autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knockdown of ALDOA in QBC939 and RBE cells attenuated the cell proliferation and induced a higher apoptosis rate. This changes could probably be attributed to the functions of ALDOA in regulating glycolysis, the epithelial-mesenchymal transition and the cell cycle, as high aerobic glycolysis activity was seen in cancer progression and this is related to the inhibition of apoptosis [20]. As demonstrated by one previous study, although oxygen was presented, cancer cells still required activate glycolysis to proliferate since glycolysis affords the majority of the materials required for large-scale cell proliferation [21].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 93%
“…35,68 Rather, investigators and practitioners are focusing their efforts on the possibility to use recombinant cytokines (at low doses and locally) to boost the anticancer activity of other immunotherapeutic regimens, including checkpoint blockers, [69][70][71][72] adoptive cell transfer, 73-76 oncolytic virotherapy, [77][78][79][80][81] DNA-and peptide-based vaccines, [82][83][84][85][86][87] dendritic cell (DC)-based interventions, [88][89][90][91][92] as well as other immunostimulatory agents like Toll-like receptor (TLR) agonists. [93][94][95][96][97] Here, we discuss recent preclinical and clinical advances in the development of recombinant cytokines for use as immunological adjuvants in cancer patients.…”
Section: Introductionmentioning
confidence: 99%